A population-based study of breast implant illness - Magno-Padron, David A.; Luo, Jessica; Jessop, Terry C.; Garlick, Jared W.; Manum, Joanna S.; Carter, Gentry C.; Agarwal, Jayant P.; Kwok, Alvin C. (Archives of Plastic Surgery, 2021)
Background Despite evidence supporting the safety of breast implants, some women associate their implants with adverse health effects and have called this syndrome “breast implant illness.” We sought to characterize breast implant illness symptoms and to report how implant removal affects their symptoms.Methods An anonymous 20 question survey was administered to the Facebook group: “UTAH Breast Implant Illness” to characterize the symptoms these women attributed to their breast implants. Several questions allowed us to evaluate how implant removal affected women’s symptoms.Results Of the 182 respondents, 97% report that implants negatively affect their health and 95% identify these symptoms with breast implant illness. Ninety-six percent of respondents had implants placed for cosmetic reasons and 51% had silicone implants. The most common symptoms associated with breast implant illness are brain fog (95%), fatigue (92%), joint pain (80%), and hair loss (74%). Sixty percent of respondents learned about breast implant illness from family/friends and/or social media platforms (56%), 40% of respondents had their implants removed, and 97% report relief of their symptoms post-removal (23% complete, 74% partial). Following explantation, there was a significant improvement in all but one reported symptom. An association was found between the number of symptoms reported prior to explantation and the number of symptoms resolving following explantation.Conclusions Breast implant illness is a syndrome characterized by fatigue, decreased focus, hair loss, and joint pain after the placement of breast implants. Nearly all patients report improvement of symptoms after implant removal. Significant efforts should be made to better understand breast implant illness and its etiology.
Keywords: Breast prosthesis implantation; Cosmetic surgery; Surgery, plastic; Adverse effects